PENGARUH LITERASI DIGITAL DAN EFIKASI DIRI TERHADAP KESIAPAN KERJA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UKI TORAJA - Mawar Evrillia; Dian Intan Tangkeallo; Mince Batara (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of digital literacy and self-efficacy on the work readiness of students of the Management Study Program, Faculty of Economics and Business, Indonesian Christian University Toraja. This study uses a quantitative approach with an explanatory research method. The research population is 231 active students of the Class of 2022, with a sample of 70 respondents determined using simple random sampling techniques. Data collection was carried out through the distribution of questionnaires, then analyzed using multiple linear regression analysis with the help of SPSS version 26. The results showed that partially digital literacy did not have a significant effect on job readiness (t = 1.330; sig. = 0.188 > 0.05), while self-efficacy had a positive and significant effect on job readiness (t = 4.942; sig. = 0.000 < 0.05). Simultaneously, digital literacy and self-efficacy had a significant effect on job readiness (F = 44.723; sig. = 0.000 < 0.05), with a determination coefficient value (R2) of 0.572. This shows that 57.2% of the variation in job readiness can be explained by digital literacy and self-efficacy, while the rest are influenced by other factors outside the study